Tra i libri di Isacco Argiro - Gioffreda, Anna (2020)
The book "Tra i libri di Isacco Argiro" provides a biographical and historical study of the figure of Isaac Argyros, a Byzantine scholar in the Palaelogan period. It has been carried out by the analysis of Argiros´ manuscripts.